Nonlinear parametric assessment of modular prefabricated steel-reinforced concrete composite column subjected to earthquake loading. (15th June 2023) - Wu, Chenglong; Chen, Sheng; Mou, Ben; Liu, Linguang; Liu, Jiming; Zhang, Jigang
Abstract: This study is intended to propose a novel bolted off-site connection for prefabricated steel-reinforced concrete composite (PSRC) column to overcome significant problems involved in the traditional precast concrete connections, such as its complicity under compacted sleeve grouting and insufficient post-cast concrete vibration. Within the context of the study, the seismic characteristics such as failure model, stiffness, and energy dissipation of five PSRC columns subjected to different axial compression and shear-to-span ratios were investigated by conducting low reversed cyclic tests. Thereafter, the accuracy of multiple finite element models (FEM) of the test specimens was verified against the experimental results. In general, the research outcomes showed that the PSRC column has a simple connection structure, efficient assembly, good bearing capacity, and hysteresis characteristics. Under the influence of different parameters, the failure position was located at the middle connection, which was the key to the overall seismic performance. Moreover, it was found that the axial compression and shear-span ratios significantly affect the seismic performance of the joints. The stiffening plate thickness, the cover plate thickness, the square steel tube width-thickness ratio and the middle connection position height greatly impacted the bearing capacity but had an ignorable influence on the ductility, energy consumption, and performance degradation. Highlights: A newly proposed PSRC column is modeled in this paper. Experiment and finite element analysis of PSRC column were carried out. Parametric analysis on the seismic performance of PSRC column was carried out.